Effect of a change to mite-free bedding on children with mite-sensitive asthma: a controlled trial. Issue 7 (July 1980) - Burr, M L; Neale, E; Dean, B V; Verrier-Jones, E R
Abstract : Twenty-one children with mite-sensitive asthma took part in a crossover randomised controlled trial of mite-free bedding. Each child was issued with a new sleeping bag and pillow for a month, and twice-daily peak flow readings were compared with those obtained during a month in the child's ordinary bedding. Seventeen of the children had higher mean peak flow readings during the period in the mite-free bedding (p < 0.01). The overall improvement was only modest, however, and some mites had appeared in most of the bedding by the end of the trial. New bedding may be helpful to patients with mite-sensitive asthma, but methods are needed to prevent colonisation by mites.